THE INFLUENCE OF VIRTUAL LABORATORY-BASED LEARNING MEDIA ON THE LEARNING OUTCOMES OF CLASS VII STUDENT OF SMP NEGERI 4 MALLUSETASI - Syerlinda Syerlinda; Muh. Tawil; Sitti Rahma Yunus (Universitas Negeri Makassar, 2024)
This study aims to determine: (1) the level of learning outcomes of eighth-grade students using virtual laboratory media and conventional media, (2) there is a difference in students’ learning outcomes who taught by using virtual laboratory-based learning media and conventional media. Sample used purposive sampling technique with a population of all eighth-grade students at SMP Negeri 4 Mallusetasi consisting of 3 classes with a total of 64 students. There are 21 students in the experimental class and 16 students in the control class. The instruments in this study were a previously validated pretest and posttest learning outcome tests in the form of multiple-choice questions through Google Form. Validity analysis applied Gregory analysis, with a consistency coefficient of 100% where indicates strong consistency of the instrument. Data analysis techniques included descriptive and inferential analysis. The results of the analysis concluded that: (1) The level of learning outcomes of students after being taught using virtual laboratory-based media is categorized as low with score 0,19 and students after being taught using conventional media is categorized as low with score 0,10 (2) There is a difference in the learning outcomes of students in the use of virtual laboratory media and conventional.